Effect of Exosomal APE1 on Sensitivity of NSCLC A549 Cells to Cisplatin - DAI Nan (Zhongliu Fangzhi Yanjiu, 2020)
Objective To investigate the effect of exosomal Apurinic aprimidinic endonuclease 1 (APE1) on the sensitivity of non-small cell lung cancer (NSCLC) cells to cisplatin(CDDP). Methods The expression of APE1 in A549 cells and its exosomes were detected by Western blot after cisplatin treatment or APE1 transfection. After PKH26 exosomal staining, laser confocal observation was carried out to observe its location in cells. Exosomes and GST-APE1 were co-cultured with A549 cells to observe the expression of GST-APE1. EXOCDDP and EXOAPE1 were cultured with A549 cells for 48h to observe their effect on sensitivity of A549 cells to cisplatin. After being co-cultured with EXOAPE1, A549 cells with APE1 knockdown were treated with APE1 functional inhibitors. The sensitivity of A549 cells to CDDP and the change of γ- H2AX protein were observed. Results A549 cells with high expression of APE1 produced the exosomes with high expression of APE1. APE1 could be absorbed by receptor cells in the form of exosomes. When EXOCDDP and EXOAPE1 were co-cultured with A549 cells, the sensitivity of A549 cells to cisplatin was significantly lower than that of the control group. The drug resistance of EXOAPE1 co-cultured cells could be reversed by APE1 base excision and repair function inhibitors. Conclusion A549 cells could transmit APE1 through exosomes to reduce the sensitivity of receptor cells to cisplatin.